Jung and the making of modern psychology : the dream of a science - Shamdasani, Sonu, 1962- (Cambridge University Press, 2003)
This book is the first comprehensive study of the origins of Jung's psychology in the context of the rise of modern psychology and psychotherapy. It reconstructs the reception of Jung's work in the human sciences, and its impact on the social and intellectual history of the twentieth century.